Evaluation of dental trauma associated with cycling accidents in a city in the south of Brazil: an observational study - Vinícius Furlan; Matheus Luis Reolon; Gabriela Oltramari Nery; Thalia Tessaro Torresan; Luciana Batista Luz; Karen Barea de Paula Duarte; Regis Burmeister dos Santos; Francisco Montagner (Revista da Faculdade de Odontologia de Porto Alegre)
Aim: to evaluate the cyclists’ profile and the frequency of dental trauma associated with cycling in a southern city in Brazil. Materials and Methods: a questionnaire was applied to 234 cyclists with at least 18 years old. The variables of interests were: sociodemographic data, data related to the profile of users, and data on the occurrence of all traumas and dental traumas. Descriptive and inferential statistical analyses were carried out (α=5%). Results: The mean age of participants was 31.38 ± 11.6 years, ranging from 14 to 67 years. The majority of the participants were male (62.8%), had attended higher education (45.7%), and had incomes equivalent to 1 to 3 times the minimum wage (39.3%). The main reason given for riding a bicycle was leisure (35.9%). Users of their own bicycles had fewer items of mandatory safety equipment fitted to their bicycles than users of rented bicycles (Student’s t test, P<0.0001). However, study participants riding their own bicycles wore personal protective equipment more frequently than renters (Student’s t test, P<0.0001). Moreover, 33.7% of the respondents reported having suffered an accident, and 25% had traumatized some part of the body. Among those who reported traumas, 20% (4/20) had suffered traumas to hard dental tissues and supporting structures. Discussion: Dental trauma was not frequent in a population predominantly from an urban area that uses bicycles, especially for leisure, despite the prevalence of accidents involving bicycle use. Conclusion: Health education campaigns should emphasize the importance of personal protective equipment for cyclists and of safety items fitted to bicycles, whether cyclists’ own or rented.